Human-AI Collaboration Models for Scalable Enterprise Software Testing - Rejenish Kiran (Malikussaleh University, Aceh, Indonesia, 2026)
Enterprise software testing organizations must balance the scalability required by continuous delivery with the contextual judgment necessary for effective quality assurance. Although automated testing enables rapid execution and extensive regression coverage, it lacks the domain expertise, business context, risk awareness, and ethical accountability required for critical release decisions. This paper proposes two complementary governance frameworks that establish a structured model for human–AI collaboration in enterprise software testing. The Human–AI Responsibility Allocation (HARA) Model defines the optimal distribution of testing activities based on comparative strengths, assigning repetitive and computationally intensive tasks—including regression testing, pattern recognition, anomaly detection, and test execution—to artificial intelligence, while reserving strategic responsibilities such as test planning, defect prioritization, release readiness assessment, governance, and compliance oversight for human experts. To operationalize this allocation, the AI Confidence-Based Escalation Framework (ACEF) introduces a three-tier escalation mechanism that dynamically determines when AI-generated testing outcomes require human review according to confidence scores, business criticality, and organizational risk tolerance. The framework further incorporates measurable governance indicators, including escalation rate, false-positive rate, human override frequency, model drift, and decision traceability, enabling continuous monitoring of AI performance and accountability. The proposed frameworks are evaluated conceptually across regulated enterprise environments, including insurance, financial services, and healthcare, where software quality directly affects regulatory compliance, operational resilience, and customer trust. The analysis demonstrates that clearly defined accountability boundaries enable organizations to achieve the speed and scalability of AI-assisted testing while preserving human judgment for high-risk decisions. The proposed governance architecture provides a practical foundation for responsible AI adoption in software quality assurance by improving testing efficiency, auditability, transparency, regulatory compliance, and organizational confidence in AI-supported continuous delivery practices without compromising human oversight or decision accountability